Handbook of polymer-modified concrete and mortars : properties and process technology - Ohama, Yoshihiko (Noyes Publications, 1995)
Describes polymer-modified mortars and concretes and covers the principles of polymer modification for cement composites, along with the process technology, applications, and properties of polymer-modified mortars and concretes. Also discusses special polymer-modified systems such as MDF cements, anti-washout underwater concretes, polymer-ferrocements, and artificial woods.
Keywords: Polymer-impregnated concrete.; Polymer-impregnated mortar.; Polymers.; elektronické knihy; electronic books